2022
DOI: 10.21203/rs.3.rs-1225167/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of Central Corneal Epithelial Thickness With Anterior Segment OCT in Patients With Type 2 Diabetes Mellitus

Abstract: Aim: The aim of this study was to evaluate the central corneal thickness (CCT) and central corneal epithelial thickness (CCET) in patients with Type 2 diabetes mellitus (DM), and the effect of the duration of diabetes, the degree of diabetic retinopathy (DR), and HbA1c level. Method: CCT and CCET values ​​of 72 patients diagnosed with type 2 DM and 72 healthy individuals were measured by anterior segment optical coherence tomography (AS-OCT). The eye tear function was evaluated with the Tear Break-up Time test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
0
1
Order By: Relevance
“…However, Lee et al found a significant increase in CCT in diabetic patients older than 10 years compared to diabetic patients younger than 10 years [14]. The duration of diabetes and the HbA1c level was not found to have any statistically significant effect on these parameters (p > 0.05) [15]. Comparing the CCT between patients with HbA1c level < 7.5% and those with HbA1c > 7.5%, we found a positive but not statistically significant correlation.…”
Section: Discussioncontrasting
confidence: 59%
“…However, Lee et al found a significant increase in CCT in diabetic patients older than 10 years compared to diabetic patients younger than 10 years [14]. The duration of diabetes and the HbA1c level was not found to have any statistically significant effect on these parameters (p > 0.05) [15]. Comparing the CCT between patients with HbA1c level < 7.5% and those with HbA1c > 7.5%, we found a positive but not statistically significant correlation.…”
Section: Discussioncontrasting
confidence: 59%